A Comprehensive Study of Islamic Law Regarding Sex Change and Enhancement Surgery - Qurrota A'yun; Asma’ Adniyyah Binti Che Ismail (Al-Fiqh: Journal of Contemporary Islamic Law, 2026)
Advancements in medical technology have intensified debates within Islamic law regarding sex reassignment and enhancement surgery. This study aims to systematically examine how Islamic jurisprudence classifies elective sex reassignment and corrective intersex surgery, including their legal consequences for lineage, marriage, inheritance, guardianship, and religious obligations. Employing a normative legal research design with a qualitative doctrinal approach, the study analyzes classical fiqh texts, contemporary juristic opinions, institutional fatwas, and maqaṣid al-shari‘ah principles through structured data condensation and comparative verification. The findings reveal that elective sex reassignment for anatomically normal individuals is consistently deemed impermissible based on the doctrine of taghyir khalqillah. In contrast, corrective surgery for intersex individuals is conditionally permissible when supported by verified medical necessity. The study’s novelty lies in constructing an integrative analytical framework linking scriptural evidence, juristic methodology, and family law implications. These findings provide structured guidance for scholars, policymakers, and medical practitioners in addressing gender-related medical interventions within Islamic law.